Brolucizumab versus aflibercept for recalcitrant diabetic macular edema in Indian real-world scenario – The BRADIR study - Debdulal Chakraborty; Ashish Sharma; Soumen Mondal; Jay Sheth; Tushar Kanti Sinha; Subhendu Boral; Angshuman Mukherjee; Ranabir Bhattacharya; Ritobroto Maitra (American Journal of Ophthalmology Case Reports)
Purpose: To compare the safety and efficacy of aflibercept with brolucizumab for recalcitrant diabetic macular edema (DME). Observations: At week 52, no significant visual improvement was noted in the eyes treated with either brolucizumab (P = 0.527) or aflibercept (P = 0.393). The CMT decreased significantly after brolucizumab therapy (P = 0.012), but not with aflibercept (P = 0.284) at 52 weeks. The proportion of patients with IRF and SRF reduced significantly in both arms. The mean number of brolucizumab injections was significantly lower (3.93[±1.28]) than aflibercept (4.75[±1.62]) (P = 0.037) over the 52 weeks. At 52 weeks, 76.67 % of eyes treated with brolucizumab attained full macular dryness (CMT<300 μm with absence of SRF and IRF) compared to 50 % of eyes treated with aflibercept (P = 0.036). Subconjunctival hemorrhage was the only adverse event observed in the study (P = 0.701); no other systemic or ocular adverse events, such as intraocular inflammation, were reported. Conclusion and importance: The BRADIR study suggests that brolucizumab might have an edge over aflibercept in visual and anatomical outcomes that lasted 52 weeks with reduced injection frequency in case of recalcitrant DME.